2016
DOI: 10.1186/s13045-016-0317-7
|View full text |Cite
|
Sign up to set email alerts
|

PEG-aspargase and DEP regimen combination therapy for refractory Epstein–Barr virus-associated hemophagocytic lymphohistiocytosis

Abstract: BackgroundEpstein–Barr virus-associated hemophagocytic lymphohistiocytosis (EBV-HLH) is the most frequent subtype of secondary HLH triggered by infections. Previous studies have shown that ~30 % or more of patients with EBV-HLH do not respond to standard therapy. This study investigated the efficacy and safety profile of a modified DEP regimen in combination with PEG-aspargase (L-DEP) as a salvage therapy for refractory EBV-HLH.MethodsIn this study from October 2014 to October 2015, 28 patients with refractory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 23 publications
(35 reference statements)
1
42
1
Order By: Relevance
“…According to previous literature, age is a negative factor for the prognosis of EBV‐HLH, and adult EBV‐HLH patients suffer poorer prognoses compared to children (Tseng et al , ; Kogawa et al , ; Arca et al , ). Our centre uses L‐DEP as a salvage treatment for relapsed and refractory EBV‐HLH, which can effectively improve the remission rate and achieve the goal of bridging to allogeneic haematopoietic stem cell transplantation (allo‐HSCT) (Wang et al , ). However, some controversies remain regarding the initial treatment strategy in EBV‐HLH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to previous literature, age is a negative factor for the prognosis of EBV‐HLH, and adult EBV‐HLH patients suffer poorer prognoses compared to children (Tseng et al , ; Kogawa et al , ; Arca et al , ). Our centre uses L‐DEP as a salvage treatment for relapsed and refractory EBV‐HLH, which can effectively improve the remission rate and achieve the goal of bridging to allogeneic haematopoietic stem cell transplantation (allo‐HSCT) (Wang et al , ). However, some controversies remain regarding the initial treatment strategy in EBV‐HLH.…”
Section: Discussionmentioning
confidence: 99%
“…Group 2: patients whose initial therapy did not include etoposide. transplantation (allo-HSCT) (Wang et al, 2016). However, some controversies remain regarding the initial treatment strategy in EBV-HLH.…”
Section: Discussionmentioning
confidence: 99%
“…For the patients with refractory EBV-HLH and no remission after the initial HLH-94/HLH-04 regimen and the patients with alleviation after the initial treatment but recurrent EBV-HLH, the available salvage treatments mainly include anti-thymocyte globulin (ATG) [20], tumor necrosis factor alpha (TNF-α) inhibitor [21], anti-CD52 monoclonal antibody [5,22], anti-CD20 monoclonal antibody [23,24], and DEP/L-DEP [25,26]. For the refractory or recurrent EBV-HLH, our previous study shows that the DEP and L-DEP regimens achieved a high treatment efficiency and prolonged the survival time of the patients, and enables more patients to undergo allo-HSCT [25,26]. In this study, our results also showed the very high treatment efficiency of the DEP and L-DEP regimens in the refractory EBV-HLH patients with no remission after HLH-94/ HLH-2004 and recurrent patients; and the therapeutic efficacy of L-DEP against EBV-HLH was higher than DEP.…”
Section: Discussionmentioning
confidence: 99%
“…There were 52 patients with initial etoposide and 14 without one. The baseline level between two group shows no differences (p > 0.05) ( Table 1) for DEP/L-DEP regimen once a week [13,15], 60-100 mg/m2 d1-d3 for E-CHOP regimen. .…”
Section: Treatment and Outcomementioning
confidence: 90%